The Effect of GHR/exon-3 Polymorphism and Serum GH, IGF-1 and IGFBP-3 Levels in Diabetes and Coronary Heart Disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2015)
Aim: The present study investigated the effects of growth hormone (GH), insulin-like growth factor-1 (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3) and GH-receptor (GHR)/exon-3 polymorphism on diabetes mellitus (DM) and coronary heart disease (CHD) patients. Patients and Methods: Ninety patients with CHD, 90 patients with DM and 96 controls were included in this study. The GH, IGF-1 and IGFBP-3 serum levels were measured with enzyme-linked immunosorbent assay. GHR/exon-3 variants were determined by multiplex-polymerase chain reaction. Results: The frequency of all alleles and genotypes in all study groups were distributed according to the Hardy-Weinberg equilibrium. In addition, any association between GHR/exon-3 variants and the presence of risk factors were detected. The blood levels of GH, IGF-1 and IGFBP-3 were not distributed according to GHR/exon-3 variants. However, in the DM group, higher levels of IGF-1 and lower levels of GH and IGFBP-3, and in CHD group lower levels of IGF-1, GH and IGFBP-3 were observed. The order of GH levels were DM<CHD< Controls; IGF-1 levels were CHD<Controls<DM and IGFBP-3 levels were CHD<DM<Controls. Conclusion: No direct effect of GHR/exon-3 polymorphism was observed in DM or CHD patients. However GH, IGF-1, IGFBP-3 and insulin were thought to act together to establish body homeostasis in patients with DM and CHD.
Keywords: Coronary heart disease; diabetes mellitus; GHR; GH; IGF-1; IGFBP-3; polymorphism; GROWTH-HORMONE GH; CARDIOVASCULAR RISK; FACTOR-I; REPLACEMENT THERAPY; DEFICIENT ADULTS; INSULIN-SECRETION; BODY-COMPOSITION; RECEPTOR GHR; GLUCOSE; METABOLISM